REFLECTIVE TEACHING DESIGN AND CASE ANALYSIS OF MATHEMATICS PROPOSITION COURSE IN MIDDLE SCHOOL—TAKE THE DECISION OF CONGRUENT TRIANGLE AS AN EXAMPLE - Shuo, Zou; Chen, Yuxin; Pereira, Jerito (UNIKA SANTU PAULUS RUTENG, 2023)
The theory of rethinking teaching originated from the European and American countries, and then it was paid attention to gradually in our country. Reflective teaching theory is an important means to enhance teachers' thinking ability and students' learning ability and improve teaching quality. Based on the overview of reflective teaching theory and its teaching strategies, the author discusses the teaching practice of reflective teaching theory in the middle school mathematics proposition lesson of the same triangle decision lesson, in order to provide reference for improving teachers' professional quality and students’ learning ability.